FLNC truncations cause arrhythmogenic right ventricular cardiomyopathy. Issue 4 (10th January 2020) - Brun, Francesca; Gigli, Marta; Graw, Sharon L; Judge, Daniel P; Merlo, Marco; Murray, Brittney; Calkins, Hugh; Sinagra, Gianfranco; Taylor, Matthew RG; Mestroni, Luisa; James, Cynthia A
Abstract : Background: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a heart muscle disease that affects predominantly the right ventricle and is part of the spectrum of arrythmogenic cardiomyopathies (ACMs). ARVC is a genetic condition; however, a pathogenic gene variant is found in only half of patients. Objective: Filamin C gene truncations ( FLNCtv ) have recently been identified in dilated cardiomyopathy with ventricular arrhythmia and sudden cardiac death, a phenotype partially overlapping with ARVC and part of the ACM spectrum. We hypothesised that FLNCtv could be a novel gene associated with ARVC. Methods: One hundred fifty-six patients meeting 2010 ARVC Task Force Criteria and lacking variants in known ARVC genes were evaluated for FLNC variants. Available family members were tested for cosegregation. Results: We identified two unique FLNCtv variants in two families (c.6565 G>T, p.Glu2189Ter and c.8107delG, p.Asp2703ThrfsTer69), with phenotypes of dominant RV disease fulfilling 'definite' diagnosis of ARVC according to the 2010 Task Force Criteria. Variants in other cardiomyopathy genes were excluded in both kindreds, and segregation analysis revealed that p.Asp2703ThrfsTer69 was a de novo variant. In both families, the disease phenotype was characterised by prominent ventricular arrhythmias and sudden cardiac arrest. Conclusion: The identification of FLNCtv as a novel cause of ARVC in two unrelated families expands the spectrum of ARVC non-desmosome disease genes for this disorder. Our findings should prompt inclusion of FLNC genetic testing in ARVC to improve diagnostic yield and testing of at-risk relatives in ARVC.